Perioperative improvement in serum albumin level in patients with left ventricular assist device. Issue 11 (16th September 2020) - Imamura, Teruhiko; Combs, Pamela; Siddiqi, Umar; Mirzai, Saeid; Stonebraker, Corinne; Bullard, Heather; Simone, Pamela; Jeevanandam, Valluvan
Abstract: Background: The negative impact of baseline hypoalbuminemia on clinical outcome following left ventricular assist device (LVAD) implantation is well known. However, the implications of perioperative change in serum albumin levels on post‐LVAD outcomes remain uninvestigated. Methods: Among consecutive patients with baseline serum albumin <3.5 g/dl who received durable LVAD implantation between April 2014 and August 2017 and were followed for 1 year, the impact of perioperative change in serum albumin level from baseline to 3 months post‐LVAD on the incidence of adverse events was investigated. Results: Sixty‐eight patients (median 60 years and 69% male) were included. Serum albumin change was an independent predictor of the occurrence of adverse events with an adjusted hazard ratio of 0.32 (95% confidence interval, 0.13–0.78) and a cutoff change of 0.7 g/dl. Those with albumin increase >0.7 g/dl had higher 1‐year freedom from adverse events (45% vs. 14%, p  = .008), dominantly due to lower incidence of death or sepsis compared with those without ( p  < .05 for both). Conclusion: Among those with baseline hypoalbuminemia, a considerable perioperative increase in serum albumin levels following LVAD implantation was associated with lower mortality and morbidity. The implication of aggressive nutrition intervention on LVAD patients is the next concern.